Factores que inciden en consumir contenidos de medios tradicionales a digitales por los futuros profesionales de la carrera de Comunicación del 2020 - Moran Barco, Alexis Javier (2020)
In this case study, the factors that influence the consumption of content from traditional to digital media will be investigated specifically for future professionals of the communication career promotion 2020, it is for this reason that a type of qualitative and quantitative research is used where it will proceed to look for bibliographic information to know basic concepts of different authors about the media, later to carry out surveys to the students of the eighth semester, parallel A and B to verify and know according to the raised topic. Once the surveys were carried out, it was possible to know that a large percentage of students prefer the digital media found on social networks and other audiovisual platforms for their consumption in terms of entertainment to participate in a certain content and thus interact with other users; expressing their point of view through writing, but in terms of informative content they prefer traditional media at the international and national level; Because the information is much more reliable, contrasted and verified, the traditional medium with the highest consumer demand would be television because apart from listening to the narrative of the information, we can observe the facts through images and videos.